LAMA PENGGUNAAN ALAT KONTRASEPSI SUNTIK 3 BULAN DENGAN PERUBAHAN BERAT BADAN PADA AKSEPTOR DI DESA GAYAMAN KECAMATAN MOJOANYAR - Yuni Susanti, Ika (JURNAL KEPERAWATAN SEHAT, 2015)
Popular types of injectable contraceptives in Indonesia is the DMPA. Working power of the old, effective and high-level reversibility make three-month injectable contraceptives become one of the options acceptor. However, each method of contraception have side effects, one of which is an increase in weight. This study aims to determine the use of a long relationship with the increase in body weight at 3-month injectable contraceptive acceptors. The type of research uses analytic research with cross sectional approach. Independent variable is the old three-month injectable contraceptive usage, and the dependent variable is the increasing weight of the injectable contraceptive acceptors three months. The study population was all of 3-month injectable contraceptive acceptors during the first year, two years, three years revisited. This research was carried out on September-November 2010, the sampling techniques used are non-probability sampling using simple random sampling to obtain a sample of 40 respondents. View of data collection techniques of secondary data and observation and statistical tests used were Spearman rank (Rho). The results from 40 respondents indicate long three-month injectable contraceptive use during the three years were 19 respondents (47.5%) and increased weight gain of 24 respondents (60%). Data analysis using Spearman Rank statistical test (Rho) showed that the level of significance ? = 0.00 (